Preparation of Sustained Release Tablet with Minimized Usage of Glyceryl Behenate Using Post-Heating Method - Kang, Changmin; Lee, Ju Hyun; Kim, Dong Wook; Lee, Beom Jin; Park, Jun Bom (AAPS PharmSciTech, 2018)
The purpose of this study was to prepare sustained release (SR) matrix tablets using a direct compression incorporated with a post-heating process. Allopurinol was selected due to the water-soluble property and Compritol 888 ATO® (also known as glyceryl behenate) was used as an SR matrix-forming agent. The API, SR material, microcrystalline cellulose, and magnesium stearate (lubricant) were mixed and prepared into a tablet by a direct compression method. The compressed tablets were stored in a dry oven at four temperatures (60, 70, 80, and 90°C) and for three time periods (15, 30, 45 min). The DSC and PXRD data indicated that the crystallinity of the API was not altered by the post-heating method. However, SEM images demonstrated that Compritol 888 ATO® was melted by the post-heating method, and that the melted Compritol 888 ATO® could form a strong matrix. This strong matrix led to the significant sustained release behavior of hydrophilic APIs. As little as 3 mg of Compritol 888 ATO® (0.65% of total tablet weight), when heated at 80°C for 15 min, showed sustained release over 10 h. The post-heating method exerted a significant influence on lipid-based matrix tablets and allowed a reduction in the amount of material required for a water-soluble drug. This will also provide a valuable insight into lipid-based SR tablets and will allow their application to higher quality products and easier processing procedures.
Keywords: Allopurinol; Delayed-Action Preparations; Excipients; Fatty Acids; Hot Temperature; Hydrophobic and Hydrophilic Interactions; Solubility; Tablets; Temperature; direct compression; dry oven; glyceryl behenate; post-heating; sustained release